Economic Dimension of Canada-EU International Relations at the Turn of XX-XXI Centuries - Goncharenko, Anatoliy (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2018)
The article studies economic dimension of Canada-EU international relations at the end of XX - beginning of XXI centuries. The causes of interdependence of two international participants of multi-directional economic cooperation are characterized. The article clarifies the influence of the EU on the international economic position of Canada. Special attention is paid to the introduction of new forms of Canada-Europe economic cooperation. У статті досліджено економічний вимір міжнародних відносин Канада-Європейський Союз наприкінці ХХ – на початку ХХІ ст. Охарактеризовані причині взаємозалежності двох міжнародних гравців в економічній співпраці в різних напрямках. Висвітлено вплив ЄС на міжнародне економічне становище Канади. Особливу увагу приділено запровадженню нових форм канадсько-європейського економічного співробітництва.